Preliminary results for downstream water-level feedback control of branching canal networks - Wahlin, Brian T., author; Clemmens, Albert J., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2002)
Over the last 40 years researchers have made various efforts to develop automatic feedback controllers for irrigation canals. However, most of this work has concentrated on feedback controllers for single, in-line canals with no branches. In practice it would be desirable to automate an entire canal network and not just one of the branches. Because the branches in a network are hydraulically coupled with each other, a branching canal network cannot be controlled by designing separate controllers for each branch and then letting them run simultaneously. Changing the gate position in one pool on one branch can affect the water levels in pools on other branches. Because of this effect, the controllers designed for each of the in-line branches of the network will interfere with each other and potentially create instabilities in the branching canal network. Thus, the controller must be designed for the network as a whole and the branching flow dynamics must be explicitly taken into account during the controller design process. This paper presents preliminary simulation results on three different downstream feedback controllers on a branching canal network. The first controller is a series of Proportional-Integral (PI) controllers, one per pool. The second is a fully centralized PI controller. The third controller uses Model Predictive Control (MPC) to determine the appropriate control actions.
USCID/EWRI conference
Downstream water-level feedback control
Not digitized by CSUL Digital Services.
Presented at the 2002 USCID/EWRI conference, Energy, climate, environment and water - issues and opportunities for irrigation and drainage on July 9-12 in San Luis Obispo, California.